Mineral ages for multi isotope system in phlogopite-bearing pyroxene granulite and felsic gneiss, the Howard Hills, Enderby Land, East Antarctica: Possible Proterozoic tectonothermal events in the Napier Complex - Miyamoto, Tomoharu; Yoshimura, Yasutaka; Dunkley, Daniel J.; Motoyoshi, Yoichi; Carson, Christopher J. (National Institute of Polar Research, 2006)
P(論文) Large mafic to ultramafic blocks in felsic gneisses on the northern part of the Howard Hills, Napier Complex, East Antarctica are accompanied by phlogopite-bearing pyroxene granulite occurring in the margins of the block. In order to understand the crustal evolution of the Napier Complex, especially regarding the thermal history after peak metamorphism, Rb-Sr, Sm-Nd and U-Pb isotopic analyses have been carried out on different minerals from the phlogopite-bearing pyroxene granulite and adjacent orthopyroxene felsic gneiss. Zircon grains from the orthopyroxene felsic gneiss yielded near concordant U-Pb isotopic ages of about 2.5Ga by conventional isotope dilution methods and defined a discordia with 2.44±0.02Ga lower intercept age. This age shows the waning stage of UHT granulite facies metamorphism in the Howard Hills. Rutile fractions from pyroxene granulite yielded a near concordant U-Pb isotopic age of about 1.5Ga. This age is interpreted as the final thermal episode, excepting local igneous intrusions, in the Howard Hills region. Fluorophlogopite fractions from pyroxene granulite yielded Rb-Sr model ages of about 1.85Ga, although evidence of retrograde metamorphism with fluid activity or deformation were poor in the pyroxene granulite. An internal Sm-Nd isochron of whole rock and orthopyroxene and feldspar separated from the same sample shows 1.85±0.15Ga. The Rb-Sr phlogopite model age, along with the Sm-Nd internal isochron age, records the time when the rocks of the Howard Hills underwent medium to high grade metamorphism at temperatures well above the currently accepted closure temperature of biotite (about 300-350°C ). departmental bulletin paper